FEATURES OF TRANSLATING METAPHORICAL PHRASES IN POLITICAL TEXTS INTO UZBEK AND ENGLISH - Abdumuratova Farangiz Alisherovna (Web of Journals Publishing, 2024)
This article explores the challenges and strategies involved in translating metaphorical phrases in political texts from English to Uzbek and vice versa. Through a comparative analysis, it investigates how cultural nuances, linguistic differences, and socio-political contexts influence the translation process. The study employs various methods to examine the effectiveness of different translation techniques, aiming to enhance cross-cultural understanding and improve the quality of political translations.
Keywords: metaphorical phrases, political texts, english, uzbek, comparative analysis.